The Effectiveness of Critical Thinking Ability in Elementary School Students Through the Discovery Learning Model in Social Science Subjects - Wijaya, Sastra; Gumelar, Gumgum; Utomo, Erry; Fahrurrozi, Fahrurrozi (Teknodika, 2023)
Through the discovery learning model, this study aims to determine the effectiveness of students' critical thinking skills in developing their self-understanding of the social environment and knowledge in the 21st-century learning era. The research results demonstrated that the learning model applied in research was suitable for developing students' critical thinking skills, as it created an active way of learning for students by finding themselves and investigating themselves. The results obtained would be loyal and long-lasting in memory, and students would not easily forget. This study employed a quasi-experimental method through a nonequivalent control group design using a quantitative research approach. In this study, the results of homogeneity calculations and significant value hypotheses (Sig 2-tailed) revealed a substantial implication of 0.000, meaning that Ho was rejected because 0.000 < 0.05 and Ha was accepted. It can be concluded that the discovery learning model could improve critical thinking skills in elementary school students.